O efeito de 10 semanas de protocolos de treinamento de força, diferenciados pelas durações das ações musculares, na resposta EMG das porções do músculo quadríceps - Frank Douglas Tourino (2016)
This study aimed to investigate the effect of a 10-week period of resistance training based on multiple sets of protocols with different durations of muscle action on the activation of the vastus medialis (VM), vastus lateralis (VL) and rectus femoris (RF) and the ratio of activations among the portions (RAAP) (VM/VL, VM/RF and VL/RF) through the report of equivalent repetitions between pre and post training. Thirty-six untrained volunteers, divided in a balanced way in three groups (5:1, 3:3 and 1:5) performed in the extensor bench knees, 3-5 sets (3 sets for weeks 1 and 2; 4 series for weeks 3 and 4; 5 series between weeks 5 and 10) 6 repetitions at an intensity 50% of 1RM, 3 min rest between sets and a repetition duration of 6 s. The protocols were distinguished only by the duration of the muscle action (AD): group 5:1 (concentric action (CON) of 5 to eccentric (EXC) 1 s), 3:3 (CON 3 s EXC 3 s), and 1:5 (CON 1 s EXC 5 s). Using the Root Mean Square (RMS), the VM, VL and RF EMG activities were recorded in each repetition of the three series of the first training session (session 2) and the first three series of the last session (session 33) representing, respectively, pre and post-training tests. The protocol practiced by the group 5:1 led to adaptive responses in all portions, with the VL and RF showed a greater number of repetitions presenting differences. Group 3:3 only the VM and RF responded to the protocol, with the VM demonstrating differences in almost all repetitions belonging to the latter half of the three series. No difference was found in group 1:5. It was verified that all the differences occurred in the latter half of the series. For the RAEP variable, differences were only identified in the 3:3 group and only in the VM/VL and VM/RF ratios. Regarding the activation variable, the main finding revealed that the increased neuromuscular demand in the final repetitions during training may have been the main factor promoting the adaptations. In addition, it was concluded that the training protocols and their respective diagnostic tests were not able to detect differences in RAEPs, probably because of the limited degrees of freedom allowed by the knee extensor apparatus.